The Subprime Mortgage Reforms: The Case of US Market - Gurcharan, S.; Wong, E.S.K.; Folk, J.Y. (Macrothink Institute, 2009)
The downfall of the mortgage industry in US has seen fingers being pointed to the government sponsored entities (Fannie Mae and Freddie Mac), while the roots cause of the formation of these entities were never closely followed. Originally the creation of the GSE was to create liquidity in the mortgage industry as part of public policy in providing housing for the middle and lower income group. Over time, resulting from a weak regulated environment saw the GSE suffering and now this left questioning the effectiveness of the initial policy.